The role of ADAMTS‐13 and von Willebrand factor in cancer patients: Results from the Vienna Cancer and Thrombosis Study. Issue 3 (6th May 2019) - Obermeier, Hanna L.; Riedl, Julia; Ay, Cihan; Koder, Silvia; Quehenberger, Peter; Bartsch, Rupert; Kaider, Alexandra; Zielinski, Christoph C.; Pabinger, Ingrid
Abstract: Essentials Cancer is associated with increased risk of developing venous thrombosis. Cancer patients were studied for ADAMTS‐13 and VWF levels and occurrence of venous thrombosis. Increased VWF in cancer patients is associated with a higher risk of venous thrombosis. Low levels of ADAMTS‐13 and/or increased VWF in cancer patients are associated with worse survival. Background: Cancer‐associated venous thromboembolism (VTE) is an important complication in the course of a malignant disease. Low ADAMTS‐13 (a disintegrin‐like and metalloproteinase with thrombospondin type 1 motif 13) and increased von Willebrand Factor (VWF) levels in cancer patients have been described numerously. Objectives: Investigation of the influence of ADAMTS‐13 and VWF on the probability of VTE and survival in malignancy. Patients/Methods: In the framework of the ongoing prospective Cancer and Thrombosis Study (CATS) ADAMTS‐13 activity and VWF antigen levels were investigated in cancer patients. Results: In total, 795 patients with various tumor types (364 female/431 male, median age 62 years) were included; of those, 56 developed VTE and 359 patients died during a median follow‐up time of 730 days. The hazard ratio (HR) of VTE per doubling of VWF level was 1.56 (95% confidence interval [CI] 1.13‐2.16) in multivariable competing risk analysis. ADAMTS‐13 levels showed no correlation with the incidence of VTE in univariate competing risk analysis. The HR of mortality per doubling of VWF level was 1.46 (95% CI 1.28‐1.66) and per SD increment of ADAMTS‐13was 0.90 (95% CI 0.81‐1.00) in multivariable Cox regression analysis. Patients with VWF >75th percentile and concomitant low (<25th percentile) or medium (25‐75th percentile) ADAMTS‐13 values had the highest probability of mortality (HR 4.31 and 4.75, respectively). Conclusions: High VWF levels were significantly associated with the risk of developing VTE in cancer patients, whereas ADAMTS‐13 was not. Low ADAMTS‐13 and increased VWF levels were independently associated with worse overall survival.